PELAKSANAAN SISTEM ZONASI PPDB TERHADAP MANAJEMEN MUTU PENDIDIKAN BERASASKAN KEADILAN DI SMP NEGERI KOTA DENPASAR TAHUN 2021 - Putu Ronny Angga Mahendra (Jurnal Komunikasi Hukum, 2022)
Education in Indonesia has actually become a special concern to see how equal access can be enjoyed by all levels of Indonesian society. In access to equity, what needs to be considered is equality of opportunity and justice in obtaining education. Efforts made by the government in realizing a quality and easily accessible education system by implementing the registration of New Student Admissions (PPDB). The implementation of New Student Admission in Denpasar City has been going very well and optimally organized. This can be seen from the making of a technical guideline as the operational basis for the school as the organizer and implementer of PPDB. The zoning line in PPDB has changed the caste of a school in society. This will certainly be able to realize the quality and quantity of our national education in a fair and equitable manner. In essence, education is the right of all children of the nation, guaranteed by the constitution and mandated in an ideal of the independence of the Indonesian nation, namely the intellectual life of the nation.